Numerical Study of the Effect of Rail Modelling Method on Train Aerodynamic Performance and Slipstream - Y. Ma; J. Zhang; J. Shi; Y. Cao (Journal of Applied Fluid Mechanics)
The high-speed movement of trains generates train-induced wind, commonly referred to as slipstream, which presents a specific safety concern for passengers and personnel. Yet, the fastening system employed to secure ballastless tracks, characterised by its complex shape, substantial quantity, and dense arrangement, remains inadequately investigated regarding its influence on train aerodynamics. In the present study, a sliding mesh technique was employed to comparatively examine the impact of different track configurations—trackless, track-only, and track with a fastening system—on the aerodynamic characteristics, slipstream formation, and wake turbulence induced by trains. The results indicate that the tracks and the fastening system increased the drag force coefficient by 0.73% and 2.05%, respectively, compared with no track. Additionally, tracks and the fastening system had a significant impact on the slipstream velocity near the train and ground. Tracks notably altered the shape of the wake near the ground, and the fastening system exacerbated this phenomenon. Further, the fastening system further intensified the generation of secondary vortices at track and footstep locations.